Pharmacokinetic profile of iron serum after ingestion of ferrous sulfate tablet 2 300 mg taken shortly after meal and 2 hours after meal in women with iron deficiency anaemia - E.Kristin M.Hakimi, S.K.Soejono L.Hakim (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Iron supplementation is a common strategy used to control iron deficiency anaemia in developing countries. Despite of that, the prevalence of anaemia is still high. Several factors causing the failure of iron supplementation program were reported. The increase in haemoglobin concentration after iron supplementation was determined by several factors, that is, the dose, iron absorption, body iron store, diet, food, and pregnancy. There had been studies on iron pharmacokinetic profile after ingestion of iron tablet taken shortly after meal compared to 2 hours after meal in healthy women, but there was no study on women with iron deficiency anaemia.Aim: The aim of this study was to find out the effect of ferrous suphate @ 300 mg taken shortly after meal and 2 hours after meal on the iron pharmacokinetic profile in women with iron deficiency anaemia.Materials and method: This study was conducted with cross-over design, so that every subject had 2 interventions with an interval (washed-out period) of 7 days. In intervention 1, ferrous sulfate tablet @ 300 mg was taken shortly after meal, and in intervention 2, the tablet was taken 2 hours after meal. Serum samples were taken serially at 0, 0.25, 0.5, 1, 1.5. 2, 2.5, 3, 4, 6, 8, 10 and 12 hours after taking iron tablets. Ferric iron concentration in serum was determined by Vitros Fe Slides method, and iron pharmacokinetic profile was determined using non-compartmental method.Result: The values of pharmacokinetic parameter from the first and second interventions were compared by t test, and the result (mean:t SEMI were: Cmox 274.25 :t 28.18 and 232.92 :t 33.25 ug/dl, T mox 3.21:t 0.30 and 4.25 :t 0.64 hours, K.0.437 :t 0.0011 and 0.3808 :t 0.0065 hour'" Kel 0.1375 :t 0.0132 and 0.1855 :t 0.0048 hour". T'/2e' 5.76 :t 0.74 and 5.81 :t 1.16 hours and AUCO-,2 2157.37 :t 264.55 and 1869.54 :t 330.60 ug/dl.hours. There are no significant differences in all pharmacokinetic parameters between both interventions.Conclusion: There are no differences in iron pharmacokinetic profiles after ferrous sulfate tablet @ 300 mg taken after meal and 2 hours after meal in women with iron deficiency anaemiaKata kunci:iron concentration, pharmacokinetics, ferrous sulfate, anemia, effect of food